Pelatihan Implementasi Pendekatan Pembelajaran Deep Learning untuk Meningkatkan Kompetensi Pedagogik Guru SD di Kota Surakarta - Atmojo, Idam Ragil Widianto; Muzzazinah, Muzzazinah; Ekawati, Elvin Yusliana; Triastuti, Rini; Isnantyo, Fajar Danur; Sukarno, Sukarno; Ramadian, Rizqi Karisma (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to improve the pedagogical competence of elementary school teachers in Surakarta City through training in implementing the Deep Learning learning approach. Pedagogical competence includes the ability to understand student characteristics, design learning, and integrate technology to create a deep and enjoyable learning experience. The implementation method of this service included counseling, practice, and individual mentoring. The evaluation instruments used were pre-test and post-test which were analyzed descriptively. The results of this service showed that as many as 20 elementary school teachers in Surakarta showed an increase in the pedagogical ability of 45% in designing and implementing deep learning strategies that focus on critical thinking, creativity, and joyful learning. With the implementation of deep learning, especially joyful learning, teachers are able to create a dynamic and meaningful learning atmosphere for students.